WATER POLLUTION ASSESSMENT IN MADIUN RIVER USING STORET METHOD - Bintang AJi Pangestu (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2021)
The Bengawan Solo River stretches from the Central Java region to East Java, making it the longest river on the island of Java, where Bengawan Solo has become the economic pulse for residents, especially in Central and East Java, which crosses trade, office areas, densely populated settlements, and industries. These various activities produce waste, which has an impact on water quality pollution. The purpose of this study aims to determine the status of the water quality standard of the Bengawan Solo River. Data used from the Solo Bengawan River Basin by using data from the January-March 2020 period through 12 monitoring points were analyzed using the STORET Method. Each parameter is analyzed using Peraturan Pemerintah no. 82 Tahun 2001 and the results most of the parameters did not meet the quality standards, including TDS, TSS, DO, Nitrite, Phosphate, COD, BOD, Lead, Copper, Total Coliform and Fecal Coliform. The results of the STORET assessment analysis show that the Bengawan Solo River is included in class 4 by 41.6% in moderate polluted conditions and the remaining 58.4% in heavily polluted conditions. The STORET Method calculation results according to classes I, 2 and 3 are 100% points in Poor condition (≥-30) which is a heavily polluted condition indicating the status of water quality is not in accordance with the standard applied by Keputusan Gubernur Jawa Timur No 61 concerning river use in East Java. Keywords: Water quality, Bengawan Solo, STORET Method